POLA SALURAN DISTRIBUSI DAN ANALISIS KELAYAKAN USAHA KOMODITI HORTIKULTURA PADA KABUPATEN MINAHASA SELATAN KECAMATAN MODOINDING - David Oscar Simatupang (Universitas Musamus, Merauke, Papua, 2016)
This Study aims to describe distribution pattern in the Market by farmer, small trader, the large trader, and broker by analyz the margin and R/C on supply chain channel of South Minahasa in District Modoinding (center commodity for vegetable) to Manado city trough costomers market. The processing and analysis is qualitative or descriptive qualitative by dividing three minds of vegetables namely potatoes, cabbage, and tomato. The research areas selected on purposive sampling it ware district Modoinding. The result showed on level of farmers, analysis commodity farming vegetable fruit (tomatoes) having R/C worth 15.7 with rate of profit of Rp. 31.805.000,- and for cabbage there isn’t efesien with R/C worth 0,35 for profit Rp 4.550.000,-. For distribution market pattern for highest margin Rp. 358.23/kg in the market for distribution channels II (Farmer – Small Traders – Market) and while for distribution channels III value Rp. 211.13/kg is the margin lowest for the market.